: № 97 (1829) (1982)
Титульного листа нет, описание составлено по обложке Для служебного пользования, экз. № 90 Экземпляры: УКП (20240506) / Инвентарный номер: АП19820152 / Сис.шифр: 65.03(2) / Авт.знак: И 93 / ГРНТИ: 06.71.03 / ББК: 65.03(2Рос.Удм)